Kerjasama Indonesia dengan Amerika Serikat dalam Peningkatan Pertahanan Udara Nasional Indonesia - Sahputra, Andi; Dermawan, Windy; Dewi, Anggia Utami (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
ABSTRACT Indonesia's air defense is one aspect that must be maintained to support the security and sovereignty of Indonesia's territory as a whole. However, until now there are still frequent violations in Indonesian airspace. The Indonesian Air Force is responsible for safeguarding Indonesia's national interests, including state sovereignty. However, in reality, this responsibility is not yet balanced with an adequate air defense system, both in terms of quality and quantity. In overcoming this, air defense cooperation with other countries that have advantages is needed, especially with the United States. This research uses qualitative research methods with data collection techniques including observation, interviews and literature study. The form of air defense cooperation between Indonesia and the United States is carried out in five forms of cooperation, namely providing TNI AU defense equipment, joint training, sending TNI AU personnel for education at various levels, sustainability programs for USA products and US Grant 333 and FMF grant programs for Airfield Resiliency Equipment and Maritime Security. There are four obstacles in Indonesia's air defense, obstacles which include the limited budget allocation of the Indonesian Air Force, the limited number of Indonesian Air Force personnel, the limited number of Indonesian Air Force defense equipment and the Indonesian Air Force's defense equipment which is not yet modern. Keywords: Bilateral, Defense Cooperation, Air Defense, Indonesian Air Force